Isoindigo‐Based Polymers with Small Effective Masses for High‐Mobility Ambipolar Field‐Effect Transistors. Issue 36 (24th July 2017) - Yang, Jie; Zhao, Zhiyuan; Geng, Hua; Cheng, Changli; Chen, Jinyang; Sun, Yunlong; Shi, Longxian; Yi, Yuanping; Shuai, Zhigang; Guo, Yunlong; Wang, Shuai; Liu, Yunqi
Abstract : So far, most of the reported high‐mobility conjugated polymers are p‐type semiconductors. By contrast, the advances in high‐mobility ambipolar polymers fall greatly behind those of p‐type counterparts. Instead of unipolar p‐type and n‐type materials, ambipolar polymers, especially balanced ambipolar polymers, are potentially serviceable for easy‐fabrication and low‐cost complementary metal‐oxide‐semiconductor circuits. Therefore, it is a critical issue to develop high‐mobility ambipolar polymers. Here, three isoindigo‐based polymers, PIID‐2FBT, P1FIID‐2FBT, andP2FIID‐2FBT are developed for high‐performance ambipolar organic field‐effect transistors. After the incorporation of fluorine atoms, the polymers exhibit enhanced coplanarity, lower energy levels, higher crystallinity, and thus increased µ e .P2FIID‐2FBT exhibits n‐type dominant performance with a µ e of 9.70 cm 2 V −1 s −1 . Moreover, P1FIID‐2FBT exhibits a highly balanced µ h and µ e of 6.41 and 6.76 cm 2 V −1 s −1, respectively, which are among the highest values for balanced ambipolar polymers. Moreover, a concept "effective mass" is introduced to further study the reasons for the high performance of the polymers. All the polymers have small effective masses, indicating good intramolecular charge transport. The results demonstrate that high‐mobility ambipolar semiconductors can be obtained by designing polymers with fine‐tuned energy levels, small effective masses, and high crystallinity. Abstract : Three isoindigo‐based polymers, PIID‐2FBT, P1FIID‐2FBT, andP2FIID‐2FBT are developed for high‐performance ambipolar organic field‐effect transistors. After the incorporation of fluorine atoms, the polymers show that an obvious mobility change from p‐channel dominant to n‐channel dominant transport characteristics. Especially, P1FIID‐2FBT exhibits a highly balanced electron/hole mobility, resulting from the fine‐tuned energy levels, high crystallinity, and relatively small effective mass.